[tex]\large\huge\green{\sf{Answer:-}}[/tex]
[tex]\large\huge\green{\sf{Given:-}}[/tex]
[tex]\large\huge\green{\sf{ToFind:-}}[/tex]
[tex]\large\huge\green{\sf{FormulaRequired:-}}[/tex]
[tex]\large\huge\green{\sf{Solution:-}}[/tex]
[tex] \red {\mathbb{ \underline { \tt Using \: quadratic\: equation \: method:-}}}[/tex]
now
[tex]x²-6x +34=0 \\ here : \\ a = 1 \: and \: b \: = - 6 \: and \: c \: = 34 \\
x = \frac{- b ± \sqrt{b {}^{2} - 4ac } }{2a}
\\ x = \frac{- (- 6 )± \sqrt{ (- 6) {}^{2} - 4 \times 1 \times 34 } }{2 \times 1} \\ x = \frac{6± \sqrt{36 - 136} }{2} \\ x = \frac{6± \sqrt{100} }{2} \\ x = \frac{{6±10 } }{2} \\ x = \frac{{6 + 10 } }{2} \: and \: x = \frac{{6 - 10 } }{2} \\ x = \frac{16}{2} and \: \frac{ - 4}{2} \\ x = 8 \: and \: \: x = - 2[/tex]